Challenge Feeding and Milk Production Performance in Crossbred Cows - Kamboj, M.L.; Mengistu, R.A.; Bindal, S.; Datt, Chander (Indian Journal of Animal Nutrition, 2018)
Ten advanced pregnant crossbred (Karan Fries) cows were randomly allotted to 2 groups of 5 each to evaluate the effect of ‘challenge feeding’ on performance and economics of milk production. The animals in control group were given standard ration while in challenge fed (treatment) group, the animals were given additional amount of concentrate mixture. The mean DMI of cows during prepartum period was similar (2.44±0.05 and 2.62±0.06 kg/100 kg BW) in both groups. However, the postpartum DMI was higher (P<0.05) in challenge fed group than in control group (3.21±0.13 vs. 2.67±0.07 kg/100 kg BW). The concentrate intake was higher during pre and post partum periods in treatment group. The overall mean daily milk yield was higher (P<0.05) in treatment group as compared to control group (20.5 vs. 17.3 kg/d). The milk composition (fat, lactose, protein and SNF content), body condition score and calf birth weight, were similar in both groups. The net income per cow per day was higher by ` 17.9 in treatment than control group. It was concluded that the challenge feeding of crossbred cows improved their production performance during early lactation and was found to be economical